A landscape analysis of enablers and barriers to digital payments to health workers during large-scale immunisation campaigns in sub-Saharan Africa: a scoping review and in-depth interviews - Vincent Micheal Kiberu; Noel Namuhani; Elizabeth Ekirapa; Juliet Aweko; Charles Opio; Fredrick Kanobe; Peter Wakholi; Timothy Abuya; Maggie Mcconnell; Ahmed Hamani; Idil Hussein Jama; Michael Ediau; et al. (Taylor & Francis Group, 2026)
Background Timely and consistent digital payment of health workers is crucial for improving the effectiveness of immunization campaigns and achieving the polio eradication goals by 2026. However, evidence on the enablers and barriers to digital payments in sub-Saharan Africa (SSA) is limited. Objective To explore the enablers and barriers to digital payments for immunization campaign health workers in eight selected SSA countries. Methods An exploratory case study using qualitative methods was conducted in eight SSA countries: four English-speaking (Uganda, Kenya, Nigeria, Ghana) and four French-speaking (Senegal, Ivory Coast, Cameroon, Democratic Republic of the Congo). A scoping review and in-depth interviews were conducted between March and May 2022 in each country. Data were analyzed thematically. Results Digital payments are rapidly expanding in SSA, including during large-scale immunization campaigns. Key enablers included supportive regulatory frameworks, increasing mobile phone and digital platform coverage, and the benefits of digital payments. Barriers included inadequate telecom infrastructure, cybercrime, challenges with customer registration, higher transaction costs, and payment delays. Conclusion This study identifies key enablers of digital payments in eight SSA countries, including supportive regulations, growing mobile phone ownership, and expanding digital platforms. Persistent challenges – such as limited infrastructure, verification constraints, and payment delays – affect implementation. Findings, while context-specific, offer valuable insights for policymakers to strengthen digital payment systems, improve verification, and enhance coordination to optimize health worker payments during immunization and public health campaigns.
Keywords: Digital payment; immunisation; healthworkers; barriers; enablers